مساهمة الوظائف الإدارية لإدارة الموارد البشرية في تحقيق جودة التعليم العالي من وجهة نظر الإداريين بالجامعات الجزائرية. - عشوش عبدالقادر; بوكروح عبدالله (جامعة الوادي University Of Eloued, 2024)
هدفت هذه الدراسة إلى التعرف على دور الوظائف الإدارية لإدارة الموارد البشرية في تحقيق جودة التعليم العالي من وجهة نظر الإداريين بالجامعات، استخدم فيها المنهج الوصفي التحليلي، والاستبيان كأداة. أشارت أهم النتائج إلى أن التطبيق الفعلي للوظائف الإدارية للموارد البشرية لا يرقى إلى المستوى المطلوب لتحقيق وتحسين الجودة، وأن مستوى جودة التعليم العالي جاء بنسبة متوسطة إلى الضعيفة وهذا راجع إلى عدم توفير المتطلبات المادية والبشرية اللازمة لتطبيق هذه الفلسفة داخل هذه المؤسسات. This study aimed to identify the role of the administrative functions of human resources management in achieving the good quality of higher education from the point of view of university administrators, in which the descriptive analytical approach was used, and the questionnaire as a tool. The most important results indicated that the actual application of the administrative functions of human resources does not rise to the level required to achieve and improve quality, and that the level of quality of higher education came at a medium to weak rate, and this is due to the lack of material and human requirements for applying this philosophy within these institutions
the contribution of the administrative function of human resources management to achieving the good quality of higher education from the point of view of administrators in Algerian universities.
Keywords: الموارد البشرية; وظائف إدارة الموارد البشرية; الجودة; جودة التعليم العالي; المؤسسات الجامعية; human resource management; human resources; functions; quality; quality of higher education; University institutions